ENHANCING SCIENCE AND TECHNOLOGY BY DECENTRALIZING DOWNWARD MANAGEMENT STYLE - Khan, Ch Talha (Advances in Social Sciences Research Journal, 2017)
The aim of this paper is to understand and review the performance of the Science and Technology in China by decentralizing the downward management style. On the basis of different studies show that China investing more in Research and Development (R&D) investment and in Science and Technology (S&T) sector that is a great indication for the betterment of economy. But still the results of these investments are not fruitful and also don’t contribute up to the expectations, and to identify the problem on the basis of literature that is downward management style. At the end enlist some suggestions to make these investments more productive